Sebuah Pemaknaan Lagu Cinta Kita milik Slank oleh Habib Novel Alaydrus sebagai Seorang Muslim - Perdana, Tazkia Anugraheni (IAINU Kebumen, 2023)
The development of technology gives rise to a new face in da'wah methods. The use of social media as a medium in spreading Islam is intensively carried out. A Da'I is required to present quality content. One of them is understanding a song by taking values that can be applied in the life of a Muslim. The song Cinta Kita is a song by the band Slank. Habib Novel tries to understand the song and provide an explanation of how the song is applied to a Muslim. The research method used is descriptive qualitative. With the main data source coming from a video lecture entitled Cinta Kita by Habib Novel. The discussion in this study includes the existence of Slank in Indonesia, the preaching of Habaib on social media, and how the meaning of the song Cinta Kita. From this research, it can be concluded that the song Cinta Kita does not only talk about the love story of male and female couples. However, it can be applied to teacher-student, parent-child, and friendship relationships. By applying it, a harmonious relationship will be established and create Heaven on earth.